HUBUNGAN PENGETAHUAN KELUARGA LANSIA TERHADAP PEMBERIAN DIIT HIPERTENSI DI DESA POJOK KECAMATAN PURWOSARI KABUPATEN BOJONEGORO - Fidrotin azizah, Fidrotin azizah; Rahmawati, Rahmawati; betty, betty (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
There are many families who do not know and understand about the diet in elderly hypertensive disease in village Corner . The general objective of this study was to determine the relationship of family knowledge of the diet of hypertension in the elderly in the Village Corner Purwosari District of Bojonegoro. The design in this study is a cross sectional correlation . The entire population is elderly with hypertension in the Village Corner Purwosari District of Bojonegoro in 2013 , as many as 63 people , with 54 samples taken by simple random sampling . After the tests were tabulated and analyzed using Spearman rho ' .  The results showed that there is a level of knowledge of family ties to the administration of the diet of elderly hypertension in the elderly . The results of the data analysis at the knowledge level of the provision of elderly family diet significant hypertension in the elderly is 0.000 which is smaller than ? is 0.05 so that H1 is accepted . From the research, it was concluded that the level of knowledge of elderly families in the village Corner associated with dietary administration of hypertension in the elderly . Efforts can be made by elderly families in preventing hypertension by performing the consumption of foods rich in dietary fruits and vegetables , low-fat milk or non-fat , and whole grains with the composition of 2,100 calories . Keywords : Knowledge , Diet , Hypertension , Elderly